Polyglot Networks:Overseas Chinese Returnees and the Establishment of Indonesian Language Programs in China, 1945–1965 - Kankan Xie (The China Review, 2025)
Language and language education are central to studies of Chinese diasporic culture. However, existing scholarship has overwhelmingly focused on how overseas Chinese populations navigate language politics in their host societies. This research adopts a different perspective by examining the crucial roles overseas Chinese played in establishing Indonesian language programs in mainland China between the mid-1940s and mid-1960s. Specifically, overseas Chinese “returnees” were indispensable in founding the National College of Oriental Studies during World War II and launching several Indonesian language programs in the early years of the People’s Republic of China. While these programs served vastly different political purposes over time, they also reveal critical yet often overlooked aspects of—and surprising continuities in—China-Indonesia cultural exchange amid decolonization, domestic conflicts, and the Cold War. Although the primary aim of these programs was to fulfill the operational needs of state agencies and government-affiliated organizations, returnee networks played essential roles in promoting Indonesian culture in China. They actively participated in circulatory cultural diplomacy between the two countries, contributing significantly to China’s long-term knowledge production on Indonesia.